The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/eat.23375
|View full text |Cite
|
Sign up to set email alerts
|

Gaining “The Quarantine 15:” Perceived versus observed weight changes in college students in the wake of COVID‐19

Abstract: Objective: Amidst restrictions to reduce the spread of COVID-19, jokes have surfaced regarding weight gain during the pandemic. The current study documents perceived changes since COVID-19 and compares these to observed longitudinal changes in reported weight, BMI, and how college students described their weight from January to April 2020. Method: Undergraduates (N = 90; 88% female) completed on-line assessments before and after students were required to leave campus due to COVID-19. Time 1 and Time 2 surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 20 publications
4
108
1
2
Order By: Relevance
“…A summary of the impact of COVID-19 on the overall change in perceived weight status, dietary behaviors, physical activity behaviors, sedentary behaviors and other lifestyle behaviors are shown in Table 2. Eleven out of 19 articles mentioned changes in weight where ten articles mentioned weight gain that ranged from 12.8% to 48.6% and six articles mentioned weight loss that ranged from 13.9-19.4% (Table 3) [2][3][4][5]18,19,21,25,26,28,29]. Two articles reported the combined proportion of participants who lost weight and did not perceive a change in weight [3,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the impact of COVID-19 on the overall change in perceived weight status, dietary behaviors, physical activity behaviors, sedentary behaviors and other lifestyle behaviors are shown in Table 2. Eleven out of 19 articles mentioned changes in weight where ten articles mentioned weight gain that ranged from 12.8% to 48.6% and six articles mentioned weight loss that ranged from 13.9-19.4% (Table 3) [2][3][4][5]18,19,21,25,26,28,29]. Two articles reported the combined proportion of participants who lost weight and did not perceive a change in weight [3,25].…”
Section: Resultsmentioning
confidence: 99%
“…While one study reported that an increased BMI predicted an increase in appetite (OR = 1.07), junk food consumption (OR = 1.03) and lower adherence to a Mediterranean diet [2], another study reported that being overweight (OR = 1.31) or obese (OR: 1.64) were significant predictors of adherence to a healthy diet [22]. Adherence to an unhealthy diet was predicted by a decrease in physical activity (OR = 2.62), living in macroeconomic regions (OR = 1.43-1.47), increased screen time (OR = 1.54) and decreased consumption of homemade food (OR = 3.06) [5,22]. • Age (>50 y OR = 0.9) (21 to 50 years old lower adherence than >50 y)…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 10 studies based on a quality assessment of the results, and 27 studies were excluded based on reasons presented in the PRISMA flow diagram (Figure 1). The range of observations covered dietary choices (14,(21)(22)(23)(24)(25)(26)(33)(34)(35)(36)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) , lifestyle changes in children (24,36,(48)(49)(50)(51) , physical activity levels (33)(34)(35)37,38,(38)(39)(40)(41)43,46,47,49,52,53,(53)(54)(55)(56)(57)(58)(59)(60) , psychosocial factors (22,23,<...>…”
Section: Categorization Of Determinantsmentioning
confidence: 99%
“…In contrast, secondary school students felt refreshed on awakening and increased sleeping hours (51) . Weight gain was reported by others to be related to decreased night time sleep and reduced physical activity time (26,41,60) Sedentary lifestyle and screen time increased during the lockdown (24,26,38,47,(55)(56)(57) . Those participants who were not currently working or those who started working from home felt that they gained more weight compared with participants who did not have a change in job routine (21,21,52,58) .…”
Section: Impact Of Confinement On Body Weightmentioning
confidence: 99%
“…Meta-analyses have confirmed that students experience significant weight gain during this time related to stress, increased alcohol consumption, unhealthy eating patterns and a more sedentary lifestyle (33) . Emerging data, including results from a single study of US college students, demonstrate increases in screen time and energetic intake and decreases in physical activity that could lead to energy imbalance during the pandemic (34) . As Sebastiano et al note, HBI initiatives in post-secondary educational institutions have the ability to alter beverage intake patterns and health during a critical time when young adults have increased autonomy over their dietary choices (6) .…”
Section: Invited Commentarymentioning
confidence: 99%